Determinação do potencial do dano ambiental causado por agrotóxicos utilizados na fruticultura irrigada do Platô de Neópolis por análise da microbiota do solo - Silva, Miralda Bezerra da (2006)
The agricultural activities effect in the natural resources degradation as that caused by the desforestation, agroquímicos soil and use erosion, is evident enough in several world regions, needing to seek sustainable agricultural systems, for this, the definition more necessary indicators necessary agricultural research, that allow monitor the environmental quality, and, therefore obtain effective solutions for different diagnosed situations. The irrigation district Platô de Neópolis, in Sergipe, owns total area of 10.432 ha., of which 7.000 ha, irrigable useful, being divided, in 27 lots, varying of 22 to 570 ha. The goal of this research was going to know the main agrotóxicos used by the producers of Platô de Neópolis through the questionnaires application with lot identification data, of the cultures and of the main agrotóxicos herbicides, insecticides and used fungicides and aplicação.Os agrotóxicos way usedder were: herbicide glifosato, insecticide malation and fungicide tiofanato methylic. To monitor agrotóxicos aggression used by the producers of the region to the fruit cultivation microbial community area was representative soils made collection of the area georeferenciado, distributed in trays for agrotóxicos application and to promote microbiota soil impact evaluation, through the technical of microbiological activity analysis made by diacetato fluoresceína hydrolisis method (FDA) and for dynamics microbial population analysis made by the soil dilution method with selective means for mushrooms, bacteria and actinomicetos that enabled the soil microbiota identification and the impact caused by agrotóxicos, once, that the microbial mass is a natural ecosystems critical component manipulated by the man. It was going used like one of the parameters the microbiological enzymatic activity, in four treatments, being, one without agrotóxico addition: soil control, with the herbicide glifosato, insecticide malation and the fungicide tiofanato metilico, for microbiological activity analysis was going made diacetato fluoresceína hydrolisis method (FDA) in different dilutions (10¹, 10² and 10 4) that verified the alterations suffered for each soil sample. Diacetato fluoresceína hydrolisis activity was effective in all treatments, and the microbiological activity was highly notable in soils that didn´t suffer no exhibition kind the treatments with agrotóxicos, the soils controls reached the biggest values in all dilutions with values between 4,16-19,92μg FDA/mim-1g-1, the rest treatments introduced an enzymatic relatively similar activity, however, the treatment with tiofanato metilico, demonstrated a considerable reduction in the enzymatic activity , obtaining values between 3,48-12,70μg FDA/mim-1g-1 representing the minor activity enzimática.Com relation to the quantification microbial population analysis, the result of mushrooms population dynamics, bacteria and actinomicetos differed statistically in function of each treatment. The mushrooms population, it went to smaller density populacional found, where the soil control, where there wasn´t agrotóxico addition belonged to 22 ufc × 10g/solo. In the soils contaminated by the insecticides constituted of: Malation a density populacional corresponding relative to 18 ufc × 10g /solo, the soil treaty with Glifosato 11 ufc × 10g /solo, under the soil treaty with Tiofanato metilico 05 ufc × 10g/solo,. Regarding actinomicetos population the smaller second population, the soils tidos like control 160 ufc x 10g/solo. In the soils contaminated by the insecticides constituted of: Malation, they introduced a density populacional corresponding to 132 ufc x 10g/solo, soil treaty with Glifosato 128 ufc x 10g/solo and under the soil treaty with Tiofanato Metilico 104 ufc x 10g/solo.A bacteria population with the biggest density populacional,o soil known as control obtained 2.225 ufc x 10g/solo. In the soils contaminated by the insecticides constituted of: Malation, they introduced a density populacional corresponding to 2.140 ufc x 10g/solo, under the soil treaty with Glifosato 1.690ufc x 10g/solo and under the soil treaty with Tiofanato Metilico 1.700 ufc x 10g/solo. Therefore, both used methods in this work, correlated, with success, like bioindicadores of the caused damage microbiota of the soil by agrotóxicos: herbicide glifosato, insecticide malation and fungicide tiofanato metilico, through the enzymatic activity determination contributing thus, like sensitive indicator to relate changes in soil microbiological properties. It was going found a community´s studied soil wide microbiological variability through the mushrooms populations, actinomicetos and bacteria and the dynamic populacional of mushrooms, actinomicetos and bacteria answered of significant form agrotóxicos exhibition with a density populacional considerable reduction, contributing thus, for a better environmental damage comprehension caused by agrotóxicos microbiota of the soil.